Endoscopic management of corrosive esophageal stenosis by temporary stent placement - Gelu-Cristian ROSIANU; Mihaela RUSU; Vasile SANDRU; Camelia DIACONU; Narcis COPCA (Archives of the Balkan Medical Union, 2018)
Introduction. Ingestion of corrosive substances often causes serious damage to the upper gastrointestinal mucosa, occasionally perforation and, in rare cases, death. Most of these events are accidental, especially in children and the elderly, and voluntary (for suicidal purposes) in adults. If the patient survives the acute episode, the long-term complications are mainly esophageal and/or gastric stenosis and esophageal cancer after 1-2 decades of evolution. Endoscopic treatment of benign esophageal stenosis consists of dilation with Savary bougies and dilation balloon, esophageal stent assembly, with the purpose of restoring esophageal luminal patency. Superior digestive endoscopy plays an important role in the evaluation of benign esophageal stenosis in terms of the severity and the extent of stenosis. Case presentation. We present the case of a 47-yearold patient admitted to our clinic for dysphagia for solid and semi-solid foods. Endoscopy revealed an esophageal stricture due to the voluntary ingestion of caustic substance with suicidal purpose, 9 months before presentation. After multiple sessions of endoscopic dilatation with Savary bougies, an esophageal stent was placed, that solved patient’s dysphagia. Conclusions. Post-caustic esophageal stenosis is a common cause of dysphagia in patients with ingestion of corrosive substances. Patients can benefit from endoscopic esophageal stent placement treatment.